Impatiens nilalohitae (Balsaminaceae): a new species from Northeastern India - Hareesh, Vadakkoot Sankaran; Sabu, Mamiyil (Phytotaxa, 2017)
Impatiens nilalohitae is described from Arunachal Pradesh, Northeastern India. The new species shows similarities with I. adamowskiana and I. rugosipetala, but differs by having a 10–15-flowered inflorescence, dark purple flowers, and four lateral sepals, among other characters. A detailed description and colour photographs, as well as remarks on geographic distribution and ecology, are provided.